What computers still can't do a critique of artificial reason - Dreyfus, Hubert L. 1929-2017 (MIT Press, 1992)
Rev. ed. of What computers can't do, 1979.
Frühere Ausg. u.d.T.: Dreyfus, Hubert L.: What computers can't do. - 1979
Keywords: Computacao (aspectos socio-economicos e politicos); Inteligencia artificial; Intelligence artificielle; Kunstmatige intelligentie; Künstliche Intelligenz; Artificial intelligence; Kritik; Mensch-Maschine-Kommunikation; Leistungsgrenze; Aufsatzsammlung